Phylogenetic analysis of the Baikalodrilus species flock (Annelida: Clitellata: Naididae), an endemic genus to Lake Baikal (Russia). Issue 4 (5th September 2019) - Martin, Patrick; Sonet, Gontran; Smitz, Nathalie; Backeljau, Thierry
Abstract: Lake Baikal is populated by an endemic genus of oligochaetes ( Baikalodrilus ), which currently comprises 24 morphospecies. The genus can be considered as a 'species flock'. However, the validity of many species is questionable: the great similarity in their description and the lack of unequivocal diagnostic characters often lead species identification to an impasse. In order to clarify the systematics of this genus, we analysed two nuclear and two mitochondrial DNA markers of 40 Baikalodrilus specimens. DNA and morphological approaches are mostly congruent in suggesting ten candidate species, although two additional species are suspected. A reassessment of the taxonomic value of the morphological characteristics of Baikalodrilus suggests that there are few that can be used as distinctive, specific criteria in the genus. The association between candidate and nominal species remains problematic, except for three species identified prior to molecular analyses. Baikalodrilus trituberculum sp. nov. is described. Phylogenetic inferences suggests that the earliest split in Baikalodrilus and the time of divergence of most lineages corresponding to species are consistent with the hypothesis of a general rearrangement of the Baikal fauna, following major environmental changes due to a general cooling in the Early Pleistocene.